A Cognitive Framework in Learning English Progressive Tense - Fahmi Aajami, Raghad (International Journal of Language and Literary Studies, 2022)
Dealing with the English language and the skills of using it is still the focus of interest for many researchers, teachers and workers in the field of education. Cognitive grammar theory founded by Langacker (1987) is one of the prominent theories in this field. Iraqi students face a problem in mastering and understanding the use of the English language tenses. There are a lot of researches that have been conducted in the Iraqi context to improve the level of Iraqi students and to benefit from cognitive theory such as analysing the polysemy of English preposition. This research is an empirical study in which 85 students from the College of Education for Women at the University of Baghdad, English department participated in this experiment. The data were collected through two tests, pre and post, and the SPSS statistical editor was used to measure the extent of improvement in the participants’ performance, in addition to a focus group discussion and questionnaire before and after the experiment. The results showed an improvement in the students’ achievement. This indicates that the cognitive grammar theory has positive contributions in improving the understanding, assimilation and use of tenses in the English as a foreign language.